CULTURALLY EMBEDDED AUGMENTED REALITY ENGLISH BOOK FOR GASTRONOMY STUDENTS ENHANCING LANGUAGE ENGAGEMENT IN HOSPITALITY EDUCATION - I Wayan Agus Anggayana; Ni Putu Lindawati; Si Putu Agung Ayu Pertiwi Dewi; I Made Arry Anggabawa (Politeknik Pariwisata Makassar, 2025)
This study explores the integration of a culturally embedded augmented reality (AR) English book to enhance language engagement among gastronomy students in hospitality education. Conducted at Akademi Komunitas Manajemen Perhotelan Indonesia with 12 culinary students, the research employed classroom observations and qualitative interviews. The AR book was designed to merge local cultural contexts, particularly Balinese and Indonesian culinary traditions, with interactive language learning elements such as 3D food models, pronunciation guides, and gamified vocabulary quizzes. Findings revealed a significant improvement in students’ motivation, vocabulary retention, and speaking confidence, with 83% of participants reporting increased engagement compared to traditional materials. Qualitative data highlighted the effectiveness of cultural relevance and multisensory interaction in sustaining attention and deepening understanding. The study concludes that AR-enhanced materials can bridge the gap between language learning and professional culinary communication within tourism and hospitality education when grounded in local culture. It recommends the broader adoption of context-sensitive digital tools in vocational programs to support linguistic and cultural competency. This research contributes to the evolving landscape of technology-enhanced hospitality education, particularly within marine and cultural tourism domains where authentic, place-based learning is essential.